Financial costs of pediatric cancer management in Africa: systematic review - Mjumbe, Criss Koba; Kulimba, Desiré Mashinda; Numbi, Oscar Luboya; Nkumuyaya, Murielle; Balimo, Diane Muatama; Diyoka, Chadrack Kabeya; Ilunga, Benjamin Kabyla (Frontiers in Public Health, 2023)
The high costs of cancer treatment and the lack of investment in health care are significant barriers to public health on the African continent. The objective of this study was to investigate the financial cost of children cancer treating in sub-Saharan Africa. We systematically searched PubMed , Cochrane, and Google Scholar to identify relevant studies between March 2000 and December 2022. We selected articles that specifically addressed the US dollar financial costs of childhood cancer in African countries. Medians and interquartile ranges ( IQR ) were calculated. We also calculated the economic burden of childhood cancer at the individual level, by dividing the direct costs of cancer per patient by the GDP per capita, PPP of the country studied. The quality of economic studies was assessed using the CHEERS 2022 28-point checklist. A total of 17 studies met our eligibility criteria. The median ( IQR ) of total childhood cancer costs by region was 909.5